2015
DOI: 10.1159/000374000
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear NMDA Receptors as a Therapeutic Target of Noise-Induced Tinnitus

Abstract: Background: Accumulating evidence suggests that tinnitus may occur despite normal auditory sensitivity, probably linked to partial degeneration of the cochlear nerve and damage of the inner hair cell (IHC) synapse. Damage to the IHC synapses and deafferentation may occur even after moderate noise exposure. For both salicylate- and noise-induced tinnitus, aberrant N-methyl-d-aspartate (NMDA) receptor activation and related auditory nerve excitation have been suggested as origin of cochlear tinnitus. Accordingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 58 publications
0
74
0
Order By: Relevance
“…The prevalence of mild tinnitus in industrial countries has been reported to be around 18% whereas 0.5% report that their tinnitus has severe negative effects on their daily life function 3 . Noise exposure has been known to be the most prevalent risk factor for developing tinnitus 4 , and it is suggested that noise-induced damage leading to tinnitus occur at the level of the inner hair cell synapse 5 . Previous studies have indicated that there is an association between the concentrations of selected stress cytokines and degrees of tinnitus severity 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of mild tinnitus in industrial countries has been reported to be around 18% whereas 0.5% report that their tinnitus has severe negative effects on their daily life function 3 . Noise exposure has been known to be the most prevalent risk factor for developing tinnitus 4 , and it is suggested that noise-induced damage leading to tinnitus occur at the level of the inner hair cell synapse 5 . Previous studies have indicated that there is an association between the concentrations of selected stress cytokines and degrees of tinnitus severity 6 .…”
Section: Introductionmentioning
confidence: 99%
“…These excitatory glutamate receptors are found in a wide range of neural cells that are responsible for opening ion channels and neural signaling. However, in the inner ear, they are found within the synapses of the inner hair cells and thought to play a role in the development of tinnitus [37]. There is significant potential for these receptors as biomarkers for neural tissues at the level of the synapse, and clinical work has already led to the identification of the therapeutic peptide Rapastinel (formally Glyx-13) as a potential therapy for tinnitus [38].…”
Section: N-methyl-d-aspartate Receptorsmentioning
confidence: 99%
“…There is significant potential for these receptors as biomarkers for neural tissues at the level of the synapse, and clinical work has already led to the identification of the therapeutic peptide Rapastinel (formally Glyx-13) as a potential therapy for tinnitus [38]. Additional work in animal models has demonstrated ribbon synapse protection from IT application of N-methyl-Daspartate (NMDA) antagonists [37].…”
Section: N-methyl-d-aspartate Receptorsmentioning
confidence: 99%
“…The treatment of hearing disorders that includes steroids [32,33], glutamate antagonist [34,35], various types of hearing aids [36][37][38], and cochlear implants [39,40]. Although these treatments produce varying degrees of improvements but they are considered unsatisfactory.…”
Section: Evidence For the Role Of Oxidative Stress In Hearing Disordersmentioning
confidence: 99%